2018
DOI: 10.21577/0103-5053.20180083
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Passion Fruit and Guava Oils from Industrial Residual Seeds and Their Application as Biofuels

Abstract: A great diversity of fruits is used in the food industry to obtain different products such as juices, sauces and foods. However, the food industry produces high amounts of residues. Passion fruit and guava are worldwide known fruits and very used by the food industry and generate tons of seed as residue. This work aims to study the extraction of oils from passion fruit and guava juice industries residues, their characterization and potential application as raw materials to obtain biodiesel and bio-oil. The pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
(19 reference statements)
0
4
0
2
Order By: Relevance
“…Only one passion fruit seed oil obtained met the requirements of Brazilian regulation regarding the oil acidity (less than 2%) for crude oils obtained by pressing (Brasil, 2021). The free fatty acid content for passion fruit seed oil observed by Wilhelm et al (2014), Chumjai & Tippayawong (2012), Kobori & Jorge (2005) and Malacrida & Jorge (2012) ranged from 0.7% to 7.35% but Iha et al (2018) reported around 50% of free fatty acid content.…”
Section: Passion Fruit Seed From Different Fruit Juice Manufacturersmentioning
confidence: 94%
See 1 more Smart Citation
“…Only one passion fruit seed oil obtained met the requirements of Brazilian regulation regarding the oil acidity (less than 2%) for crude oils obtained by pressing (Brasil, 2021). The free fatty acid content for passion fruit seed oil observed by Wilhelm et al (2014), Chumjai & Tippayawong (2012), Kobori & Jorge (2005) and Malacrida & Jorge (2012) ranged from 0.7% to 7.35% but Iha et al (2018) reported around 50% of free fatty acid content.…”
Section: Passion Fruit Seed From Different Fruit Juice Manufacturersmentioning
confidence: 94%
“…The use of passion fruit seed oil by pharmaceutical and cosmetics segments, as well as the properties of its bioactive components and their potential beneficial role for human health were extensively reviewed by Lucarini et al (2019) and Corrêa et al (2016). This oil was also evaluated as biofuel by Iha et al (2018). In Brazil, there is a demand for dried passion fruit seeds that are marketed as a decorative element for desserts as well as for passion seed oil and for recovery of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente, a extração de óleos em sementes de frutos representa uma alternativa para redução do desperdício de resíduos agroindustriais, agregando valor sustentável aos subprodutos da industrialização. Esses óleos variam quanto às suas características físico-químicas e organolépticas, de acordo com seu fruto de origem e com o método de extração utilizado (IHA et al, 2018). Dentre os métodos tradicionalmente utilizados para a obtenção de óleos de sementes, encontram-se a extração mecânica e por solventes orgânicos (ALI, M; WATSON, IA.…”
Section: Tecnologia Dos Alimentos Aplicada Ao Aproveitamentounclassified
“…An example was from passion fruit, a tropical fruit plant widely grown in northern Thailand (Tippayawong and Chumjai, 2012). Household industry, the fiber pulp and passion fruit juice will be produced into fruit juice while the seeds will be discarded and that was found to have high oil content in a range of 19-30% by weight, which may be used to produce biodiesel (Iha et al, 2018). The tung tree is a species of Vernicia in the spurge family native to southern China, Laos, Myanmar and Vietnam.…”
Section: Introductionmentioning
confidence: 99%